Implementation of fingerprint biometric template system in embedded software design - Zakaria, Nor Farizan (2006)
Reliable personal identification is necessary due to the growing importance of information technology and the necessity of protection and access restriction. The key task is to verify the person is who they claim to be. A biometric security system verifies user identity by comparing the behavioral or physiological trait possessed by the user to a previously stored sample of the trait. Fingerprints are the oldest and most widely used form of biometric identification. Local characteristic called minutiae points represent fingerprints. This project proposed an embedded software design of fingerprint biometric authentication system that involved interface design and software development in an embedded processor. The system consists of two components; the Graphic User Interface (GUI) on a host PC and the Fingerprint Biometric Template system on the Field Programmable Gate Array (FPGA) development board. The GUI will access the image repository and display the output image at each processing steps. The Fingerprint Biometric Template System contains three stages; image processing, feature extraction and matching stage. The image processing stage will enhance and skeletonized the fingerprint image, the feature extraction stage will extract the valid minutiae points in template based, and the matching stage will match the template with a previously stored template. An embedded software system that can verify the minutiae templates extracted a fingerprint image is resulted from this project